Sistem Pakar Untuk Diagnosa Penyakit Ayam Pedaging - Kusrini, Wiwik; Fathurrahmani, Fathurrahmani; Sayyidati, Rabini (Universitas Hamzanwadi, 2020)
Tanah Laut Regency is the largest producer of broilers in South Kalimantan. However, public knowledge about symptoms and diseases in chickens is still lacking, so this is a problem that must be resolved because it can cause losses. Therefore, this research was conducted with the aim of overcoming this problem, namely by building an expert system application that can be used by the public and extension workers to diagnose chicken disease. The method used to build this system is a waterfall with the forward chaining technique as a forward-looking solution, meaning that inference is done by looking for input data in the form of symptom data in the form of chicken disease. The system built is equipped with features that display disease treatment and prevention solutions based on the symptoms that have been entered, so that disease-stricken chickens can be handled appropriately and quickly according to their disease. Based on blackbox testing carried out by involving potential users, the results obtained that all functionality can work as expected. Accuracy testing is also done by comparing manual calculations with an accuracy value of 95%. This is influenced by the weighting of the symptom value which affects the decrease in the value of the symptom result when compared to ideal conditions. In conclusion, the implications of using this system can make it easier for the community and instructor to diagnose chicken disease.